Pengaruh Brand Perception dan Customer Engagement terhadap Purchase Intention pada Live Streaming Commerce Yves Saint Laurent Beauty Indonesia - Mutia Eka Wardani; Baroroh Lestari; Lina Budiarti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growth of live-streaming commerce has encouraged companies to leverage social media as a more interactive marketing strategy. As a luxury brand, Yves Saint Laurent (YSL) Beauty Indonesia has begun using TikTok Live as a marketing platform with the potential to influence brand perception, customer engagement, and consumer purchase intention. This study aims to analyze the influence of brand perception and customer engagement on purchase intention in YSLBeauty Indonesia’s live-streaming commerce. This study was a quantitative study using an explanatory research approach. Data were collected via a questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with SPSS 25. The results indicated that brand perception had a positive effect on purchase intention (p = 0,003 < 0,05), while customer engagement also had a positive effect (p = 0,003 < 0,05). Simultaneously, both variables had a positive effect on purchase intention, with an F-calculated value of 59.357 and a coefficient of determination (R²) of 0.550. Based on the research findings, it can be concluded that brand perception and customer engagement have a positive effect both individually and collectively on purchase intention in YSL Beauty Indonesia’s live-streaming commerce. Customer engagement has a greater influence than brand perception, therefore, it needs to be continuously optimized through engaging interactions during live streams.